The Electrical characterization of sodium cadmium borate glasses doped with TiO2 - Raheja, Sonam; Singh, Ravinder; Uddin, Moin (PREPARE@u® | IEI Conferences, 2021)
A glass series sodium cadmium borate glasses doped with titanium has been formed using melt quench technique within the composition 20Na2O-(20-x)CdO- 60B2O3-xTiO2 (0 ≤ x ≤ 5 mol%). The composition was prepared to study the effect of dopant (TiO2) on physical, optical and electrical properties of the glass series under study. The results of physical parameter i.e. density and molar volume show some structural changes at higher concentration of TiO2 doping. Some theoretical optical parameter parameters (n, Rm, αm and ) were calculated and displayed in Table 2 & 3. The dc conductivity of the glasses is found temperature dependent. The conductivity value ranges in between 2.45x10-6 – 3.47x10-6 Scm-1 at 523 K temperature indicates the insulating behavior of these glasses.